1995
DOI: 10.2307/2410318
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Selection on Life Span in Drosophila melanogaster

Abstract: An important issue in the study of the evolution of aging in Drosophila melanogaster is whether decreased early fecundity is inextricably coupled with increased life span in selection experiments on age at reproduction. Here, this problem has been tackled using an experimental design in which selection is applied directly to longevity. Selection appeared successful for short and long life, in females as well as males. Progeny production of females selected for long life was lower than for short-lived females t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
111
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(117 citation statements)
references
References 29 publications
5
111
0
1
Order By: Relevance
“…The evolved lineages were derived more recently (2010) from a wild population and were maintained for ∼100 generations under conditions that allowed them to reproduce indefinitely. As increased extrinsic mortality reduces longevity in Drosophila and increases fecundity (Rose and Charlesworth 1980;Zwaan et al 1995;Stearns et al 2000), it would be expected that the lineages with the shortest life spans would also have the highest fecundity (as observed). Similarly, the stock flies were kept under a regime that only allowed 3 d for breeding, whereas the breeding vials in the evolved populations were removed only after 25 d, again potentially selecting for higher fecundity (as observed).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The evolved lineages were derived more recently (2010) from a wild population and were maintained for ∼100 generations under conditions that allowed them to reproduce indefinitely. As increased extrinsic mortality reduces longevity in Drosophila and increases fecundity (Rose and Charlesworth 1980;Zwaan et al 1995;Stearns et al 2000), it would be expected that the lineages with the shortest life spans would also have the highest fecundity (as observed). Similarly, the stock flies were kept under a regime that only allowed 3 d for breeding, whereas the breeding vials in the evolved populations were removed only after 25 d, again potentially selecting for higher fecundity (as observed).…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, the predator-evolved flies tended to have higher fecundity than the control-evolved flies. Those lineages with higher extrinsic mortality (e.g., predator-evolved) tend to evolve more rapid senescence and higher fecundity (Zwaan et al 1995;Stearns et al 2000). Similarly, predator-evolved flies evolved delayed emergence in the absence of predators compared with control-evolved flies.…”
Section: Discussionmentioning
confidence: 99%
“…Negative genetic correlations have been demonstrated between reproductive effort and resistance to infection (e.g., Cotter et al 2004; Simmons and Roberts 2005; Graham et al 2010). Experimental evolution, with selection for either increased reproductive effort or resistance to infection, has resulted in coinciding decreases in resistance to infection and reproductive effort, respectively (e.g., Boots and Begon 1993; Zwaan et al 1995; Luong and Polak 2007). Additionally, trade-offs can occur due to the immediate nutritional and metabolic costs of maintaining and utilizing these traits and their physiological linkage (Sheldon and Verhulst 1996; Lochmiller and Deerenberg 2000; Sadd and Schmid-Hempel 2009; Schwenke et al 2016); allocating resources towards defense against infection necessarily diverts resources away from reproductive effort and vice versa .…”
Section: Introductionmentioning
confidence: 99%
“…Extended longevity has been shown to have a cost in reproduction at benign temperature (reviewed in Rose, 1999;Partridge et al, 2005;Le Bourg, 2007;Paaby & *Correspondence: E-mail: pablosambucetti@ege.fcen.uba.ar Schmidt, 2009;Flatt, 2011). Studies of experimental evolution showed that selection for increased life span results in an increase in late-age reproduction and that this increase is correlated with a reduced reproduction early in life at benign temperature (Rose & Charlesworth, 1980;Luckinbill et al, 1984;Rose, 1984;Zwaan et al, 1995;Scannapieco et al, 2009). However, some studies suggest that longevity and early reproduction can sometimes be uncoupled (Kengeri et al, 2013;Khazaeli & Curtsinger, 2013;Wit et al, 2013;Tarin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%